Analysis of the impact of forest fires: Pre-wedding incident of Mount Bromo and its disaster risk - Nugraha, Mayabella Puspita (Calamity: A Journal of Disaster Technology and Engineering, 2025)
Background: Forests play a crucial role in sustaining the environment, economy, and society by acting as carbon sinks that help mitigate climate change and maintain ecosystem balance. However, forest fires remain a growing global concern, including Indonesia. One significant fire occurred in Bromo Tengger Semeru National Park (TNBTS) in 2023, sparked by human negligence during a pre-wedding photoshoot. The fire damaged 1,487 hectares of land and threatened local biodiversity and ecosystems. TNBTS is home to over 1,000 plant species and holds cultural significance for the Tengger Community, who depend on its resources for their livelihoods. The research examines the environmental, economic, and social impacts of fire, using a quantitative research approach. Mentods: The methodology uses quantitative analysis using Landsat 8 imagery to assess fire severity. The Delta Normalized Burn Ratio (dNBR) is used to assess fire damage, while vegetation density is analyzed using the Normalized Difference Vegetation Index (NDVI) to ensure data reliability. Findings: The fire caused significant environmental damage. Economically, the tourism sector was severely affected, with the park’s closure for 13 days leading to an 80% drop in hotel occupancy, resulting in an estimated loss of IDR 89.76 billion. Socially, the Tengger people suffered, as the fire damaged sacred sites and disrupted their cultural practices. Also, it increases the stress and anxiety of society that depends on tourism and agriculture. Public concern about the incident underscored the importance of responsible behavior in national parks, this can be seen by Google Trend. Conclusion: Although signs of recovery are evident, the long-term ecological and economic impacts require continued assessment and mitigation efforts to ensure the sustainable future of TNBTS. Novelty/Originality of this article: This article offers a novel analysis of the Bromo Tengger Semeru National Park fire by integrating remote sensing data with environmental, economic, and social impacts, including the unique use of Google Trends to measure public concern.